High Levels of Morbidity and Mortality Among Pediatric Hematopoietic Cell Transplant Recipients With Severe Sepsis: Insights From the Sepsis PRevalence, OUtcomes, and Therapies International Point Prevalence Study*. Issue 12 (December 2017) - Lindell, Robert B.; Gertz, Shira J.; Rowan, Courtney M.; McArthur, Jennifer; Beske, Florian; Plunkett, Adrian; Weiss, Scott L.; Thomas, Neal J.; Nadkarni, Vinay M.; Fitzgerald, Julie C.
Abstract : Objectives: Pediatric severe sepsis is a major cause of morbidity and mortality worldwide, and hematopoietic cell transplant patients represent a high-risk population. We assessed the epidemiology of severe sepsis in hematopoietic cell transplant patients, describing patient outcomes compared with children with no history of hematopoietic cell transplant. Design: Secondary analysis of the Sepsis PRevalence, OUtcomes, and Therapies point prevalence study, comparing demographics, sepsis etiology, illness severity, organ dysfunction, and sepsis-related treatments in patients with and without hematopoietic cell transplant. The primary outcome was hospital mortality. Multivariable logistic regression models were used to determine adjusted differences in mortality. Setting: International; 128 PICUs in 26 countries. Patients: Pediatric patients with severe sepsis prospectively identified over a 1-year period. Interventions: None. Measurements and Main Results: In patients with severe sepsis, 37/567 (6.5%) had a history of hematopoietic cell transplant. Compared with patients without hematopoietic cell transplant, hematopoietic cell transplant patients had significantly higher hospital mortality (68% vs 23%; p < 0.001). Hematopoietic cell transplant patients were more likely to have hospital acquired sepsis and had more preexisting renal and hepatic dysfunction than non–hematopoietic cell transplant patients with severe sepsis. History of hematopoietic cell transplant, renal replacement therapy, admission from inpatient floor, and number of organ dysfunctions at severe sepsis recognition were independently associated with hospital mortality in multivariable analysis; hematopoietic cell transplant conferred the highest odds of mortality (odds ratio, 4.00; 95% CI, 1.78–8.98). In secondary analysis of hematopoietic cell transplant patients compared with other immunocompromised patients with severe sepsis, history of hematopoietic cell transplant remained independently associated with hospital mortality (odds ratio, 3.03; 95% CI, 1.11–8.27). Conclusions: In an international study of pediatric severe sepsis, history of hematopoietic cell transplant is associated with a four-fold increased odds of hospital mortality after adjustment for potential measured confounders. Hematopoietic cell transplant patients more often originated from within the hospital compared to children with severe sepsis without hematopoietic cell transplant, possibly providing an earlier opportunity for sepsis recognition and intervention in this high-risk population. Abstract : Supplemental Digital Content is available in the text.